ORGANOLEPTIC QUALITY OF BROILER MEAT THAT GIVING DRAGON FRUIT WATER EXTRACT - I G. M. D. A., Wijaya; Sriyani, N.L.P; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of giving dragon fruit peel water extract in drinking water on the organoleptic quality of broiler meat.  The design used in this study was a completely randomized design (CRD) with 4 treatments and 4 replications each consisting of four broilers.  The treatments used were P0 (drinking water without dragon fruit peel water extract as a control), P1 (2% dragon fruit peel water extract in drinking water), P2 (4% dragon fruit peel water extract in drinking water), and P3 (6% dragon fruit peel water extract in drinking water). The variables observed were color, aroma, texture, taste, and overall acceptance. The results showed that administration of dragon fruit peel water extract 2%, 4%, 6% through water drinking on the organoleptic quality of broiler meat was significantly different (P<0.05) on color, aroma, texture, and overall acceptance, while the taste was not significantly different (P>0.05). 6% extract of dragon fruit peel water through drinking water can improve the organoleptic quality of broiler meat on color, aroma, texture, and overall acceptance, but does not affect the taste.   Keywords: broiler chicken, dragon fruit skin, organoleptic quality